2019
DOI: 10.1117/1.nph.6.4.040501
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated potassium channels are critical for infrared inhibition of action potentials: an experimental study

Abstract: Thermal block of unmyelinated axons may serve as a modality for control, suggesting a means for providing therapies for pain. Computational modeling predicted that potassium channels are necessary for mediating thermal block of propagating compound action potentials (CAPs) with infrared (IR) light. Our study tests that hypothesis. Results suggest that potassium channel blockers disrupt the ability of IR to block propagating CAPs in Aplysia californica nerves, whereas sodium channel blockers appear to have no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 31 publications
0
45
1
Order By: Relevance
“… 1 3 IR-mediated modulation of excitable tissues has been demonstrated in a wide range of promising clinical applications, such as cochlear prostheses, 4 , 5 brain stimulation and mapping, 6 9 cardiac pacing, 10 and neural monitoring during surgery. 11 , 12 The main biological processes induced by pulsed IR light are attributed to the spatiotemporal thermal transients generated by water and tissue absorption, 13 which in turn can alter the membrane capacitance, 14 17 membrane resistance, 18 , 19 ion channel activities, 19 25 and intracellular calcium dynamics. 6 , 26 30 The temperature-sensitive transient receptor potential channels have received particular attention due to their intrinsic temperature sentisitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 3 IR-mediated modulation of excitable tissues has been demonstrated in a wide range of promising clinical applications, such as cochlear prostheses, 4 , 5 brain stimulation and mapping, 6 9 cardiac pacing, 10 and neural monitoring during surgery. 11 , 12 The main biological processes induced by pulsed IR light are attributed to the spatiotemporal thermal transients generated by water and tissue absorption, 13 which in turn can alter the membrane capacitance, 14 17 membrane resistance, 18 , 19 ion channel activities, 19 25 and intracellular calcium dynamics. 6 , 26 30 The temperature-sensitive transient receptor potential channels have received particular attention due to their intrinsic temperature sentisitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The consensus is that the INI results from temperature-dependent changes of passive membrane properties as well as sodium and potassium ion channel kinetics. 19 24 Due to the precise localization of IR light application and the size of experimental animals, most studies using IR light to inhibit peripheral nerves target a relatively small portion of the nerve. 19 21 , 24 Moreover, IR light application to peripheral nerves involves intercepting propagating APs that are depolarized by a strong charging current and typically take off from a resting membrane potential.…”
Section: Introductionmentioning
confidence: 99%
“…The average power is 1.15 watts for the 2 Ω resistance of the coil driven by a 50% duty time square pulses. www.nature.com/scientificreports/ Previous studies on invertebrate axons have found that the operating temperature in mollusks ranges from freezing temperature to 40 °C 51 , and a more than 20 °C of local temperature is needed for thermal blockage of the unmyelinated squid giant axon 52 . Heat blockage in myelinated axons happens at around 50 °C in mammalian myelinated nerves in cats 53 .…”
Section: Discussionmentioning
confidence: 99%
“… 18 Recently, we showed that temperature increases lead to rate increases in Hodgkin–Huxley gating mechanisms so that the channel activation rate overwhelms the channel activation rate. 19 , 20 We have modeled, experimentally demonstrated, and mathematically proven that IR inhibition can preferentially block action potential propagation in small-diameter sensory fibers. 5 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 We have modeled, experimentally demonstrated, and mathematically proven that IR inhibition can preferentially block action potential propagation in small-diameter sensory fibers. 5 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%